(untitled) (Journal of Informatics Education and Research, 2026)
The growing integration of generative artificial intelligence (GAI) into organizational systems is reshaping the strategic role of human resource management (HRM). While prior research largely examines functional applications of AI in recruitment, training, and performance management, limited attention has been devoted to how generative AI influences the microfoundations of dynamic human resource capabilities. Addressing this gap, this conceptual article integrates insights from dynamic capabilities theory, microfoundations research, and emerging scholarship on AI-enabled HR systems to develop a structured explanatory framework. The framework positions generative AI as an embedded enabler within HR systems, rather than as a peripheral technological tool. It conceptualizes HR analytics as a translational infrastructure through which AI-generated insights are institutionalized into sensing, seizing, and reconfiguring processes. Additionally, leadership agility is introduced as a contextual condition shaping the effectiveness and sustainability of AI-enabled HR transformation.